Variability of selected characteristics in sets of buckwheat, millet and amaranth; selection of perspective genotypes and comparison of their nutritive value - Anna MICHALOVÁ (Acta Agriculturae Slovenica, 1998)
During the past three years, evaluation has been carried out in the sets of buckwheat, millet and amaranth, and  the selected morphologic and phenologic characters, productivity and nutritional value were assesed. The highest variability level at particular varieties within all three crop sets was observed in the yield (coefficient of variation for buckwheat - CV= 37%, millet - CV= 16.3%, amaranth - CV= 32.2%). Other characters under study showed the medium variability level. Within the crop sets under experiment the most productive genotypes were selected for further research and for the utilisation. The nutritional value parameters were divided into four groups: I. Main quality characters (crude protein, oil and starch content), II. Content of essential fatty acids, III. Content of essential amino acids, IV. Content of mineral compounds. The basic differences become evident in the nutritional value of buckwheat, millet and amaranth in the characters of groups I. and II., and as to the content of  essential amino acids. No differences were found in the buckwheat and millet indices of group IV.  (content of mineral compounds).